The Character Alteration of Maleficent From Sleeping Beauty into Maleficent Movie - Nurhalidasia Nurhalidasia; Rosmah Tami; Nasrum Nasrum (Jurnal Adabiyah: Humanities and Islamic Studies, 2016)
This thesis studied about postmodernism from Sleeping Beauty movie into Maleficent movie. The objective of the research was to analyze the alteration of Maleficent in both movies. The writers conducted the research by using descriptive comparative method. Technique of data collection used note taking technique with theory of postmodernism by Linda Hutcheon. The writers found that there is a way that might others see character Maleficent movie is different from earlier in the Sleeping Beauty movie. It is in Historical Representation.